Sources, distribution, behavior, and detection techniques of microplastics in soil: A review - Yu-chen Yan; Zhong-fang Yang (China Geology)
In recent years, the problem of environmental pollution caused by microplastics has attracted widespread attention. This paper reviews the latest research progress in terms of the source, content and distribution characteristics, harm, and detection technology of soil microplastics by referring to the relevant literature on soil microplastics worldwide. It concludes that: (1) Existing studies worldwide have detected the presence of microplastics in soil, water, and atmosphere, and the use of agricultural films, sewage sludge, and other man-made activities are the main sources of microplastics in soil; (2) microplastics can adsorb heavy metals, persistent organic pollutants and antibiotics in soil, change the physical and chemical properties of soil. This will result in composite pollution and harm to the ecosystem; (3) microplastics in soil not only can destroy the activity of key soil microorganisms, but also enter the body of crops and soil animals, affecting normal growth of crops and soil animals, and further threaten human health; (4) at present, there is no unified operating standard for the sampling, processing, and detection process of microplastics. Analysis methods such as visual inspection, spectroscopy, and thermal analysis have both advantages and disadvantages, and emerging detection technologies require urgent development. Microplastics have become a new pollutant in soil and their distribution characteristics are closely related to human activities. They pollute the environment and threaten human health through the food chain. Although related research on soil microplastics has just begun, it will become the focus of research in the future.©2023 China Geology Editorial Office.